The Role of Industrial Relations Mediators in Resolving Termination of Employment (PHK) Disputes between Employers and Workers with Fixed-Term Employment Agreements (PKWT) that are not registered at Manpower Office of Palembang City - Mahalia Suryani (Journal of Research in Social Science and Humanities, 2025)
Mediators can help both employers and workers understand each other's positions and find a fair compromise in accordance with legal provisions. The issues addressed in this study are: 1) What is the role of Industrial Relations Mediators in resolving disputes related to the termination of employment (PHK) between employers and fixed-term workers (PKWT) not registered with the Manpower Office in Palembang?; and 2) What are the legal consequences of termination of employment (PHK) for PKWT workers who are not registered with the Manpower Office in Palembang? This research is a normative-empirical study based on primary data (field research findings) and secondary data (literature sources).The study results show that: 1) The role of Industrial Relations Mediators in resolving PHK disputes between employers and PKWT workers who are not registered with the Manpower Office in Palembang can be viewed from three perspectives: first, the normative role, where the mediator enforces existing legal norms; second, the ideal role, where the mediator seeks to resolve disputes in a fair and ideal manner; and third, the factual role, where the mediator adapts solutions to the actual conditions in the field. In this context, mediators play a crucial role in ensuring justice for workers and ensuring that employers understand the importance of registering contracts to avoid future issues; 2) The legal consequences of PHK for PKWT workers not registered with the Manpower Office in Palembang include: first, unclear legal status regarding the employment relationship, which can make it difficult to prove workers' rights, potentially rendering the PKWT contract void by law; second, harm to workers, as they do not receive optimal legal protection; third, sanctions for employers, who may face administrative penalties; and fourth, unlawful PHK procedures, where workers are entitled to claim their rights through legal channels.